Religious Dimension of Conflict and UN Peacebuilding in Central African Republic - Raharjo, Wahyu Arif (Journal of International Relations, 2024)
Despite being political, violent conflict in Central African Republic (CAR) have always had hidden dimensions that include ethnic and religious ones and this dimension resurfaced in recent development. This paper aims to assess the deliberation of religious dimension of conflict in UN Peacebuilding efforts while engaging civil society in its peacebuilding efforts and find out what these offices could do in empowering civil society participation in conflicts where religious dimension persists, to prevent further recurrence of violent conflict. Using CAR conflict as a case study, this paper will first observe religious dimension and the importance of engaging religious actors in peacebuilding. Second, drawing information from BONUCA and BINUCA as the manifestation of UN's peacebuilding activities in CAR as well as the nature of CAR conflicts, it will then seek to explore these offices engagement of religious actors as part of civil society involvement in UN peacebuilding effort. Third, the position of religious players and consideration of religious/faith-based aspect of conflict will be analysed and see what prospect it could bring in tackling violent conflict and what the UN could do. In helping CAR, UN PBC have the potential to play a central role in bridging both international community with material resources and religious leaders in domestic level with potential to build a bottom-up peacebuilding process.